Modern non - medicamental technologies of the pregravidar preparation of women - L. V. Tsallaqova; L. V. Maisuradze; F. U. Magaeva; D. K. Alborov; I. V. Kabulova (Кубанский научный медицинский вестник, 2014)
The results of pregravidar preparation of women with the use of physiotherapeutic and local natural factors are examined in the article. The women with infertility, endometriosis, premature pregnancy and women suffered from obstetric and gynecologic operations were examined. The influence of the used methods of treatment on the central and peripheral links of reproductive system was estimated. It was proved the high therapeutic effect of the developed system of the reproductive function rehabilitation while pregravidar preparation of women, which allowed to reach the restoration of fertility and the improvement of patients' standard of living.